Eskalasi Kemampuan Kognitif Melalui Imaginative Thingking dan Experience Directly - Finadatul Wahidah (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Cognitive is a child's ability to think or know something. Cognitive development refers to the ability of a child to understand something. Cognitive is a process and product of the mind for knowledge in mental activities such as remembering, symbolizing, categorizing, solving problems, creating, and fantasizing. Given the importance of cognitive development for children, teachers and parents are very important and responsible for carrying out educational interactions in developing students' cognitive abilities. The focus of the research in this study is 1) How to improve the cognitive ability of early childhood in the symbolic thinking aspect?, 2) How to increase the cognitive ability of early childhood in the egocentric thinking aspect?, and 3) How to increase cognitive ability in early childhood in intuitive thinking aspect?. This study indicates the escalation of cognitive abilities in early childhood using number cards with the following details: 1) Improved cognitive abilities of symbolic thinking aspects by using imagination techniques (Imaginative Thinking). 2) Increasing the cognitive ability of egocentric thinking by using imagination techniques and egocentric language (Imaginative Thinking and egocentric language). 3) Increasing cognitive abilities in intuitive thinking aspects, namely by providing direct experience to children (experience directly)